A Review on Service Quality in the HEI’s and its Impact on Students Satisfaction (International Journal of Food and Nutritional Sciences, 2022)
Importance of service industries was increased tremendously in the recent decade. Now the economy of our country largely depend on the service sector industry, which was earlier depended on the agriculture industry. HEindustry which helps to build the youth of the nation. Delivering quality education or service especially in the HE is the most challenging task. As the change is only the constant factor, rest others keep changing continuously. The expectation of the students is dynamic in nature studying in the college, which keeps on changing day after day. The various parameter of service quality is also dynamic. So there is a intense need to do the constant research on this particular domain. There are various models or conceptual framework already developed to analyze the service quality in the industries. The present study will identify the various aspects of service quality which is specific for the higher educational industry. Providing better service quality in HEI’s results in building the skilled manpower which are able to earn income through the Job, business or any other sources. The main elements involved in the service delivery mechanism are service provider and students. The new dimension identified is behavioural intention which measure the student satisfaction level in the HEI’s